Characterization of Homozygous Hb Setif (HBA2: c.283G>T) in the Iranian Population. (2nd January 2016) - Farashi, Samaneh; Garous, Negin F.; Vakili, Shadi; Ashki, Mehri; Imanian, Hashem; Azarkeivan, Azita; Najmabadi, Hossein
Abstract: Hemoglobin (Hb) variants are abnormalities resulting from point mutations in either of the two α-globin genes ( HBA2 or HBA1 ) or the β-globin gene ( HBB ). Various reports of Hb variants have been described in Iran and other countries around the world. Hb Setif (or HBA2 : c.283G>T) is one of these variants with a mutation at codon 94 of of the α2-globin gene that is characterized in clinically normal heterozygous individuals. We here report clinical and hematological findings in two homozygous cases of Iranian origin for this unstable Hb variant.